Diversity of Mammals in 8 Years of Jati (Tectona grandis Linn. f) Unggul Nusantara (JUN) - Tun Susdiyanti; Ken Dara Cita; Nia Yuliani; Noval Diantama; Dwi Agus Sasongko (Universitas Nusa Bangsa, 2023)
Mammals had several ecological functions and roles. The existence of mammals plays an essential role in the balance of natural ecosystems. The Experimental garden in Cogreg Village is one of the possible places to become a habitat for a diversity of mammals. The diversity of mammals found and identified in the Cogreg Experimental Garden consists of 6 types: Pteropus vampyrus, Tupaia javanica, Callosciurus notatus, Rattus argentiventer, Herpestes javanicus, and Suncus murinus, with a total of 165 individuals. The mammal habitat found in the Cogreg Experimental Garden is secondary forest or JUN Forest (Tectona grandis Linn. f) with INP Index of 195.91%.Keywords: Diversity; Mammals; Cogreg; HabitatKeanekaragaman Mamalia pada Tegakan Trubusan Jati (Tectona grandis Linn. f) Unggul Nusantara (JUN) Umur 8 TahunABSTRAKMamalia memiliki beberapa fungsi dan peran ekologis. Keberadaan mamalia sangat berperan penting dalam keseimbangan ekosistem alam. Kebun Percobaan di Desa Cogreg adalah salah satu tempat yang memungkinkan untuk menjadi habitat bagi keanekaragaman mamalia. Keanekaragaman mamalia yang ditemukan dan teridentifikasi di Kebun Percobaan Cogreg terdiri dari 6 jenis mamalia Pteropus vampyrus, Tupaia javanica, Callosciurus notatus, Rattus argentiventer, Herpestes javanicus, dan Suncus murinus dengan jumlah total keseluruhan 165 individu. Habitat mamalia yang terdapat di Kebun Percobaan Cogreg yaitu hutan sekunder atau hutan tegakan Jati (Tectona grandis Linn. f) Unggul Nusantara (JUN) dengan indeks nilai penting (INP) sebesar 195,91%.Kata Kunci: Keanekaragaman; Mamalia; Cogreg; Habitat